Observation and Modeling of Optical Emission Patterns and Their Transitions in a Penning Discharge. (22nd August 2007) - Klepper, C. C.; Hazelton, R. C.; Barakat, F.; Keitz, M. D.; Verboncoeur, J. P.
Abstract : A Penning discharge tube has been used as the excitation source for optical detection of gaseous species concentrations in a neutral gas. This type of diagnostic has been primarily used in magnetic fusion energy experiments for the detection of minority species in the effluent gas (e.g., for helium detection in a deuterium background). Recent innovations (US Patent no. 6351131, granted February 26, 2002) have allowed for extension of the operation range from< 1 Pa to as high as 100 Pa and possibly beyond. This is done by dynamically varying the gauge magnetic field and voltage to keep the optical signals nearly constant (or at least away from a nonlinear dependence on the pressure). However, there are limitations to this approach, because the Penning discharge can manifest itself in a number of modes, each exhibiting a different spatial emission pattern. As a result, varying the discharge parameters can cause the gauge to undergo transitions between these modes, disrupting any intended monotonic dependence of the overall emission on the varied parameter and hence any predicable impact on the emission. This paper discusses some of the modes observed experimentally using video imaging of the discharge. It also presents a first successful application, a particle-in-cell (PIC) code, to simulate these modes and a mode transition. The hope is that a good understanding of the physics involved in the mode transitions may allow for methods of either avoiding or suppressing such transitions. This would aid in broadening the use of this plasma-based sensor technology.